Effect of different recovery modalities on anaerobic power in off-road cyclists - Bielik, V. (Biology of Sport, 2010)
Despite massage being widely used by athletes, opinions its effects on performance recovery differ. The aim of the study was reveal the effects of passive recovery (PR), sport massage (SM) and active recovery (AR) after series of Wingate anaerobic test (WAnT) on peak power (PP) and mean power (MP). Eleven junior off-road cyclists performed warm up on the cycle ergometer followed by 3 bouts of WAnT interspersed with 4 min rest. After 20 min of PR, SM or AR subjects performed fourth WAnT in random order one week apart. There was no significant difference in PP between PR and SM (875.5 ± 56.2 vs. 921.6 ± 50.8 W) but significant difference between PR and AR (875.5 ± 56.2 vs. 970.2 ± 68.9 W; p<0.05). Significant differences were also found for MP between PR and AR (678.4 ± 45.2 vs. 746.1 ± 47.0 W; p<0.05) but not for PR and SM (678.4 ± 45.2 vs. 714.6 ± 32.8 W). Blood lactate concentration after intervention was significantly different only between trials with PR and AR (13.3 ± 2.9 vs. 7.4 ± 3.9 mmol•L-1; p<0.01) and between SM and AR (14.6 ± 3.0 vs. 7.4 ± 3.9 mmol•L-1; p<0.01). A one-way ANOVA with repeated measure indicated that AR presents better modality in reducing blood lactate or renewal PP and MP than PR and SM.